MANAJEMEN POLA ASUH DALAM MENUMBUHKAN KARAKTER KEMANDIRIAN ANAK USIA DINI - Sholihah, Imro'atus (IHTIROM : Jurnal Manajemen Pendidikan Islam, 2023)
Journal This aim For develop character independence child age done early through pattern nanny educator.Continue will explained in a number of problem as following : (1) How to plan pattern foster in the development of the character of early childhood independence ; (2) How is the implementation of parenting style in development character independence child age early; (3) How evaluation pattern foster in development character independence child age early. Research This use study Approach Qualitative Descriptive . Whereas Technique data collection using observation,interview,and documentation . And technical data analysis using Triangulation Source And Engineering . Results study This in focus planning is all teachers and staff are capable plan task with ok . First drafting vision , mission , and goal , define pattern foster And appropriate activities with an annual program and semester program so results from planning the can achieved in accordance with already goals programmed specifically For independence child . Whereas in implementation institution the make values character independence child specifically independence physical , social , and emotional . Institution use pattern foster democratic in develop independence child , with method field trip . Whereas evaluation done through evaluation curriculum, that is here teacher evaluation and students. Teacher evaluation is carried out every semester, three month And One week . Whereas evaluation student held every day through habituation And learning . From the results independence student surrendered to guardian student every One meter very attached in book report development student